The functional anatomy and connectivity of thought insertion and alien control of movement. (March 2015) - Walsh, Eamonn; Oakley, David A.; Halligan, Peter W.; Mehta, Mitul A.; Deeley, Quinton
Abstract: Alien control phenomena are symptoms reported by patients with schizophrenia whereby feelings of control and ownership of thoughts and movements are lost. Comparable alien control experiences occur in culturally influenced dissociative states. We used fMRI and suggestions for automatic writing in highly hypnotically suggestible individuals to investigate the neural underpinnings of alien control. Targeted suggestions selectively reduced subjective ratings of control and ownership for both thought and movement. Thought insertion (TI) was associated with reduced activation of networks supporting language, movement, and self-related processing. In contrast, alien control of writing movement was associated with increased activity of a left-lateralised cerebellar-parietal network and decreased activity in brain regions involved in voluntary movement, including sensory-motor hand areas and the thalamus. Both experiences involved a reduction in activity of left supplementary motor area (SMA) and were associated with altered functional connectivity (FC) between SMA and brain regions involved in language processing and movement implementation. Collectively these results indicate the SMA plays a central role in alien control phenomena as a high level executive system involved in the sense that we control and own our thoughts and movements.